A NEW SPECIES OF DIPLODISCUS TURCZ. (TILIACEAE), RELATED TO BROWNLOWIA ROXB. - AJGH Kostermans (BRIN Publishing (Penerbit BRIN), 1992)
Diplodiscus longipetiolatus Kosterm. is described based on a specimen collected in East Kalimantan.